Mothering in the Face of Genocide: A Maternal Theory Approach to The Barefoot Woman - GOWSALYA, p; JOTHI, c (International Journal of Language and Literary Studies, 2025)
Scholastique Mukasonga’s The Barefoot Woman serves as a powerful testimony of maternal resilience and cultural preservation amid the Rwandan Genocide. Central to the narrative is Stefania, the author’s mother, whose maternal role transcends traditional caregiving to embody a form of cultural and psychological resistance. Using maternal theory as a framework, this study explores Stefania’s efforts to shield her family, safeguard Rwandan cultural practices, and impart resilience during the genocide's harrowing events. Maternal theory offers insights into the intricate connections between motherhood, memory, and trauma, framing Stefania’s actions as both protective and generative. Her daily practices, such as weaving mats, preparing traditional meals, and retelling stories, serve as acts of defiance against cultural erasure. These maternal acts are further examined through the lens of trauma theory, highlighting Stefania’s role as a stabilizing force within the chaos of genocide. This paper situates Mukasonga’s narrative within the broader discourse on maternal resilience and genocide literature. The findings emphasize Stefania’s portrayal as a maternal archetype who preserves cultural identity under extreme duress, redefining the concept of motherhood in African literature. The study contributes to understanding the intersections of gender, trauma, and cultural memory, emphasizing the maternal figure’s centrality in preserving heritage during crises.